Book Review: Marjo Lindroth; Heidi Sinevaara-Niskanen & Monica Tennberg (eds.) Critical Studies of the Arctic: Unravelling the North, 2022. Cham: Palgrave Macmillan. XII, 283 p, hardcover. ISBN 978-3-031-11119-8. - Kangasluoma, Sohvi (Polar Record, 2023)
Non peer reviewed